A Brief Survey on English Textbooks for Indonesian Primary Students - Anna Marietta Da Silva; Magdalena Kartikasari Tandy Rerung (Universitas Bunda Mulia, 2020)
Within the last four years there have been an increasing number of English textbooks for Indonesian primary students. The rising number of the books in the market seems to answer the demand of both Indonesian students and teachers of English as it is now a local load subject with standard of competences set up by Ministry of Education and Culture. Yet, many if not most of the English textbooks are written from the authors’ points of view, which may not be reflective of children’s world. Furthermore, the textbooks provide target language materials that are beyond the competencies. Therefore, this article, as part of a project of writing English textbooks for children, will briefly evaluate the available English textbooks for Indonesian primary students, grades 1 to 3. It was found that out of eight English textbooks randomly evaluated, only three that provided language content that really considered the children’s language development, and the fact that Indonesian primary students are young beginners learning English, a language that is their second or even third language.